Real-life vaccination coverage in Slovak children with rheumatic diseases - Balažiová, Barbora; Kuková, Zuzana; Mišíková, Daša; Novosedlíková, Katarína; Dallos, Tomáš (Frontiers in Pediatrics, 2022)
Background Evidence-based recommendations for vaccination of patients with pediatric rheumatic diseases (PRDs) are available, their implementation in practice is unknown. Objectives To analyze real-life vaccination coverage in children with PRDs and identify reasons for incomplete vaccination. Methods Up-to-date information on vaccination status of Slovak children followed at a tertiary pediatric rheumatology center was retrieved from pediatricians over an 18-month period and compared to the standard Slovak Immunization Schedule. Reasons for missed vaccinations were analyzed retrospectively. Results Vaccination records of 156 patients (median age 10 years, 2–18) with PRDs (JIA n = 108, systemic diseases n = 21, autoinflammatory diseases n = 16, uveitis n = 9, others n = 2) were available for analysis. 117 (75.0%) were completely vaccinated, 2 (1.3%) had not received any vaccine due to reasons unrelated to PRD. 37 (23.7%) remaining patients missed altogether 48 mandatory vaccinations. In 58.3% (n = 28, in 24 patients) no PRD related reasons for missing vaccinations were identified. Only 20 vaccinations (18 live-attenuated and 2 non-live in 19 patients) were missed due to ongoing immunosuppressive treatment or PRD activity. Patients aged 11–14 years were more likely to be incompletely vaccinated than other age groups (48.8% vs. 15.9%, p < 0.001), mainly due to missed MMR booster. Systemic immunosuppressive treatment was a significant predictor for incomplete vaccination status (OR 5.03, 95% CI 1.13–22.31, p = 0.03). Conclusion Full vaccination is possible in a high proportion of PRD patients. In addition to immunosuppressive therapy, reasons unrelated to PRDs are a frequent and possibly inadequate cause of missed vaccinations. Periodic vaccination status assessments are needed in pediatric rheumatology care.